Comment faire réaliser des activités scientifiques et technologiques à l'école primaire ? - CLAUDINE LARCHER (Metaichmio Publications, 2009)
We briefly present the context of science education in France when « la main à la pâte » began in 1996 in order to reform the teaching of science and technology at primary school. Then, we analyse the propositions offered in the frame of this dealing comparing with the knowledge about teaching and learning descended from didactic researches.